FACTORS CONTRIBUTING TO MULTIPLE PERSONALITY DISORDER ONSET - Menka kumari (International Journal of Multidisciplinary Research and Studies, 2021)
Multiple personality disorder is a complex mental condition that is most likely brought on by a combination of factors, such as chronic stress, exposure to traumatic events, and prolonged participation in abusive relationships. As a direct result of the ailment itself, the individual who is afflicted with multiple personality disorder may, on occasion, have been put in precarious situations when they were still developing as a child and adolescent. An individual's personal history of traumatic events, particularly those that were experienced repeatedly, were overwhelming, or threatened their lives when they were children, can almost always be traced back to the development of multiple personality disorder in that individual. This is the case in approximately 99% of all cases.